Derby, Kansas: cold war boomtown - Robertson, Margaret (Kansas State University, 2010)
This thesis explores the development of Derby, Kansas, from the arrival of its first settlers in 1869 through the early 1970s. During its first seventy-five years, Derby never grew beyond its origins as a tiny trade center for local farmers, its economic growth constantly stymied and overshadowed by the often explosive growth of Wichita, twelve miles to the north. Derby might have met the fate of so many other Kansas farming communities that did not survive developments in industrialized agricultural and transportation in post-World War II America. With the beginning of the Cold War, however, the federal government began pouring money into the Midwest and West, building up existing, and constructing new, military installations. In addition, federal spending spurred massive new defense industries, creating growth around the cites of what some historians have called “Gunbelt America.” Wichita was one such city. Derby’s proximity to Wichita finally worked to its advantage, and the small town experienced its own boom as it became a residential community inhabited by affluent commuters to the job opportunities nearby. In addition, Derby’s racial homogeneity, its relative affluence, and the deliberate attempts of its boosters to portray it as a “family friendly,” that is, as a white, middle-class, community, further spurred its growth as Wichita went through the turmoil of school desegregation in the 1960s and early 1970s. Derby, Kansas, illustrates a distinct category in the development of the new Gunbelt West, a community that flourished both because of its proximity to a larger city as well as its distance from the perceived turmoil of that urban center.
Keywords: Derby, Kansas; Kansas; Military history; suburbs; History, United States (0337)